Effects of a metabolic syndrome induced by a fructose-rich diet on bone metabolism in rats - Felice, Juan Ignacio (2014)
Objective. The aims of this study were: first, to evaluate the possible effects of a fructose rich diet (FRD)-induced metabolic syndrome (MS) on different aspects of long bone histomorphometry in young male rats; second, to investigate the effects of this diet on bone tissue regeneration; and third, to correlate these morphometric alterations with changes in the osteogenic/adipogenic potential and expression of specific transcription factors, of marrow stromal cells (MSC) isolated from rats with fructoseinduced MS. Materials/Methods. MS was induced in rats by treatment with a FRD for 28 days. Halfway through treatment, a parietal wound was made and bone healing was evaluated 14 days later. After treatments, histomorphometric analysis was performed in dissected femoral and parietal bones. MSC were isolated from the femora of control or fructose-treated rats and differentiated either to osteoblasts (evaluated by type 1 collagen, Alkaline phosphatase and extracellular nodule mineralization) or to adipocytes (evaluated by intracellular triglyceride accumulation). Expression of Runx2 and PPARγ was assessed by Western blot. Results. Fructose-induced MS induced deleterious effects on femoral metaphysis microarchitecture and impaired bone regeneration. Fructose treatment decreased the osteogenic potential of MSC and Runx2 expression. In addition, it increased the adipogenic commitment of MSC and PPARγ expression. Conclusions. Fructose-induced MS is associated with deleterious effects on bone microarchitecture and with a decrease in bone repair. These alterations could be due to a deviation in the adipogenic/osteogenic commitment of MSC, probably by modulation of the Runx2/PPARγ ratio.